Formação de professores para prevenção do abuso sexual infantil - Ferreira, Michelle Fernanda (Universidade Federal de São Carlos, 2019)
Child sexual abuse is characterized as one of the most cruel forms of child abuse, since the victim's practice carries with it profound marks that directly affect child development. Thinking about this complexity, it became necessary to reflect on how teachers in Brazil have been trained to deal with sexual abuse and contribute to its prevention. The objective of this research was to analyze and understand what were the tools/skills and resources used by them in the prevention of child sexual abuse. As a result, the study points out that there were several tools avaiable that contributed to coping with sexual violence, such as psychoeducation, modeling techniques, social skills training, sexuality education, as well as storytelling. With regard to teacher training, the results showed that the theme was present in continuing teacher training, however, there is a lack of discussions in initial training. Studies carried out by Garbin et al. (2010) and Martelli (2013), showed an absence of discussions within the University, since there are no disciplines in the curricula of undergraduate courses that specifically deal with sexual violence, this explains the lack of academic work in the educational field and consequently the professionals' unpreparedness in dealing with abuse cases.
Teacher training to prevent child sexual abuse
Keywords: Violência intrafamiliar; Intrafamilial violence; Abuso sexual infantil; Child sexual abuse; Formação de professores; Teachers training; Contação de histórias; Storytelling; CIENCIAS HUMANAS::PSICOLOGIA::TRATAMENTO E PREVENCAO PSICOLOGICA